Can Market-Based Environmental Regulation Promote Green Technology Innovation? Evidence from China - Qu, Fang; Xu, Lei; Chen, Yufeng (Frontiers in Environmental Science, 2022)
To alleviate climate change and environmental issues, China has implemented many environmental regulation policies. This paper takes the SO2, carbon emission trading pilot (SETP, CETP) in China as the quasi-experiment, and under the difference-in-difference framework, studies whether market-based environmental regulation (MER) policy promotes green technology innovation. The investigation is conducted employing patent data with the “IPC Green Inventory” on panel data of China’s 278 prefectural-level cities over the period 2003-2017. We found that (1) as for a single policy, SETP successfully promoted green technology innovation, but fail in CETP, which shows that not all MER policies can play a positive effect on green technology innovation. Meanwhile, SETP and CETP did not change the direction of technology innovation and had no impact on total technology innovation. (2) For the combination policy, SETP and CETP failed to jointly promote green technology innovation, and the current MER policy in China is difficult to realize the policy combination effect. This result implies that repeated implementation of similar environmental policies failed to stimulate innovation. (3) Heterogeneity analysis shows that the promotion effect of SETP on green technology innovation mainly in the eastern region, and the promotion effect on invention patents is more prominent than utility model patents, which shows that green technology has improved not only in quantity but also in quality. These findings provide empirical evidence and policy implication for the efficient implementation of environmental regulation.